A content analysis of the teacher-pupil verbal interaction of a level II class at the Manila Youth Reception Center - Aguinaldo, Jose Espiritu 1948-; Adorio, Mercedes P. (Quezon City College of Education, University of the Philippines Diliman, 1976)
A content analysis of teacher-pupil verbal interaction was conducted in a Level II class at the Manila Youth Reception Center. Using a model suggested by John Hansen, the study analyzed the prevalent mental processes used by the teacher and pupils for five days in a social studies class. The results showed a preponderance of category 1 (seeking information) and category 2 (giving information) interaction.
Vita.
Thesis (Master of Arts in Teaching Special Education - Behavioral Sciences)--University of the Philippines, Diliman
Keywords: Interaction analysis in education -- Philippines; Content analysis (Communication); Teacher-student relationships -- Philippines; Social sciences -- Study and teaching -- Philippines